A Pyrazolate-Supported Fe(3)(μ(3)-O)-Core; Structural, Spectroscopic, Electrochemical and Magnetic Study - Piñero, Dalice (2007)
A comparison is made between the structural, spectroscopic and magnetic properties of pyrazolate versus carboxylate complexes containing the Fe(3)(μ(3)-O)-motif. [Image: see text]